APPLICATION OF GEOGRAPHIC INFORMATION SYSTEMS (GIS) TO DETERMINE THE STATUS OF MANGROVE ECOSYSTEMS OF MODUNG REGION MADURA - Zainul Hidayah (Jurnal Kelautan, 2014)
Conversion of mangrove forests to fish ponds and settlements area has been occurred at Modung region for many years. In addition, human activities in making use of mangrove’s leaves for cattle food was also a factor that could cumulatively affect the condition of mangrove ecosystems. To maintain and conserve the ecosystems, the existing condition of mangrove’s area need to be assessed by employing relevant methods. Objectives of this study were to analyze the present condition of mangrove forests and to verify the critical status in the study area. Geographic Information Systems (GIS) was used in this study as a tool to analyze and to map the ecosystem status. GIS technology was employed because its ability to map the distribution of mangrove’s habitat based on satellite imagery data as well as to determine its status using several criterias.  According to the Landsat Imagery data, total areas of mangroves forest were 92,76 Ha. Moreover, using 2 different methods (remote sensing and field measurements), approximately 77% of mangrove ecosystems in the area can be classified as critical.Key Words: Mangroves, GIS, Modung Madura